THE IMPLEMENTATION OF FLASHCARDS TO TEACH SPOKEN FUNCTIONAL TEXT TO EIGHTH GRADERS - Rani Linggar Purga Hardiyanti,; Restu Arini, (JOEL: Journal of Educational and Language Research, 2023)
The purpose of this study was to evaluate the speaking abilities of SMPN 4 Yogyakarta students of class VIII by using a descriptive quantitative research. Students from class VIII at SMPN 4 Yogyakarta were the population of this study, and class VIII E students made up the sample. A test was employed as a research tool in this study. The Pretest and Post-Test scores from two tests are compared to determine how Flashcards support students' speaking development. The result shows, (1) learning spoken functional text using flashcard media in class was declared successful with an average score of 81.71 in the post-test because it meets the Passing Grade standards of the school. The average pretest data (M = 74.77) and the average post-test data (M = 81.71); (2) There are significant results in the class posttest score with 0.000 Sig. value (2-tailed) (p < 0.05); (3) Flashcard learning media is appropriate in improving students' speaking performance as it reduces boredom and produces fun learning for students